New Uzbekistan and Political Reform: The Role of National Strategies In Strengthening Governance - Sobirovich, Turdiyev (Indonesian Journal of Public Administration Review, 2025)
This article analyzes the significance of key national development strategies that have played a crucial role in shaping Uzbekistan’s state policy, namely the “2017-2021 Action Strategy,” the “2022-2026 Development Strategy,” and the “Uzbekistan – 2030 Strategy.” The study examines how these strategies contribute to democratic development, judicial and legal reforms, economic growth, and social progress. Additionally, the article highlights the principles of “transparency and accountability in governance, the protection of human rights, the eradication of forced labor, and the outcomes of judicial reforms.” These development plans create foundations to establish New Uzbekistan, elevated public welfare, and efficient state administration through progressive reform initiatives.